Pengaruh Karakter Eksekutif, Karakteristik Perusahaan dan Corporate Governance Terhadap Tax Avoidance pada Perusahaan Properti dan Real Estate Yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2019 - I Gusti Ayu Agung Milla Cahyaninggaluh; Luh Kade Datrini; L. G. P. Sri Eka Jayanti (Jurnal Riset Akuntansi Warmadewa, 2022)
This study aims to analyze the effect of executive character, company characteristics and corporate governance on tax avoidance in property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2016-2019. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange in 2016-2019, with a total sample of 172 respondents. Techniques in data collection using observation and literature study. The data analysis technique used multiple linear regression analysis. The results show that the executive character has a positive effect on taxes on property and real estate companies listed on the IDX in 2016-2019. Company characteristics have a positive effect on tax avoidance in property and real estate companies listed on the IDX in 2016-2019. Corporate governance has no effect on tax avoidance in property and real estate companies listed on the IDX in 2016-2019.